2012
DOI: 10.1016/j.tsf.2011.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Low-thickness high-quality aluminum nitride films for super high frequency solidly mounted resonators

Abstract: We investigate the sputter growth of very thin aluminum nitride (AIN) films on iridium electrodes for electroacoustic devices operating in the super high frequency range. Superior crystal quality and low stress films with thicknesses as low as 160 nm are achieved after a radio frequency plasma treatment of the iridium electrode followed by a two-step alternating current reactive magnetron sputtering of an aluminum target, which promotes better conditions for the nucleation of well textured AIN films in the ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…In order to examine the microstructure of the Al 1−x Sc x N, SEM was used for planar and cross‐sectional imaging of the samples. Typically, the well c ‐axis oriented Al 1−x Sc x N shows pebble‐like surface morphology . Figure (a) and (b) show the films grown with N 2 /(Ar + N 2 ) = 50% concentration.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to examine the microstructure of the Al 1−x Sc x N, SEM was used for planar and cross‐sectional imaging of the samples. Typically, the well c ‐axis oriented Al 1−x Sc x N shows pebble‐like surface morphology . Figure (a) and (b) show the films grown with N 2 /(Ar + N 2 ) = 50% concentration.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies already discussed a lot about the characterization of high quality AlN and AlScN: typically, such films would have pebble-like surface morphology [1,14,15,25,26] and homogeneous columnar structure [19,30] can be observed in cross-section. Additionally, 000l (l ¼ 2, 4, 6) reflections in XRD 2θ/θ scan [4] and low rocking curve FWHM values indicate high degree of c-axis orientation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High resolution TEM analyses have shown that these ultrathin fi lms have a fi ne columnar texture and a continuous lattice microstructure within a single grain from the interface with the Mo layer through to the AlN surface, thus confi rming the presence of a strong orientation even in the 25-nm-thick fi lm. 65 Preliminary characterizations of these ultrathin AlN fi lms performed in collaboration with Polytechnic University of Madrid (solidly mounted BAW resonators), 62 University of California-Berkeley (Lamb wave resonators), 68 and University of Pennsylvania piezoelectric nanoelectromechanical actuators) 10 , 69 validate the study's potential as a technological base by which to further increase operation frequency and overall performance of different types of electroacoustic devices.…”
Section: 67mentioning
confidence: 88%
“…Although sputtering has the advantage of growing AlN at a lower temperature than other AlN growth techniques, such as molecular beam epitaxy (MBE) and metal organic chemical vapor deposition (MOCVD), it is not a conformal growth process and compromises the material quality. The rocking curve FWHM of sputtered AlN is more than 1°, compared to MOCVD or MBE AlN of a few hundred (100-1000) arcsec, and is not designed to control thickness at the atomic scale [4,[6][7][8][9]. Thus, the current challenge is to grow a good-quality, uniform, conformal and thin AlN layers on metals or patterned devices at relatively low temperatures.…”
mentioning
confidence: 99%